Prototipe Sistem Rekomendasi Tempat Wisata Menggunakan Algoritme Simple Additive Weighting (SAW) - Sibarani, Alexander J. P.; Amalia, Suci; Larasati, Fadya (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Tourism is a strategic sector that can drive economic growth in various regions, including North Sumatra, which offers diverse tourism potential. However, tourists often face difficulties in selecting destinations that match their preferences and needs. Each tourist has different characteristics and preferences, such as facilities, number of visitors, ticket prices, and quality of services, which become the main considerations when choosing a destination. Therefore, a decision support system is needed to provide destination recommendations based on these criteria. This study aims to design a prototype web-based decision support system using the Simple Additive Weighting (SAW) method, which can offer tourism recommendations according to user preferences. The SAW method was chosen to assess the predetermined criteria accurately. In this study, four main criteria facilities, number of visitors, ticket prices, and service quality are used as the basis for decision-making. The results of this research show that the decision support system prototype was successfully designed and can provide tourism recommendations in North Sumatra based on tourists’ preferences. This system is expected to assist tourists in choosing the most suitable travel destination based on their specific needs.